Effects of the time of administration and the concentration of exogenous prostaglandin F on ovulation in pacu (Piaractus mesopotamicus) - Sato, Rafael Tomoda [UNESP]; de Abreu, Mariana Roza [UNESP]; Kuradomi, Rafael Yutaka; de Jesus Silva, Laíza Maria [UNESP]; Batlouni, Sergio Ricardo [UNESP] (My University, 2024)
In an effort to improve the spawning success rate in hypophysed pacu (Piaractus mesopotamicus) females, we investigated the effects of the time of administration and the concentration of Ciosin® (i.e., an analogue of prostaglandin F2α (PGF2α)) on ovulation. To that end, in Experiment 1, hypophysed females received 2 mL/fish of ciosin either at the time of the resolving dose (0H) or at five (5H) or seven hours (7H) postresolving dose. Then, in Experiment 2, hypophysed females were induced at the time of resolving the dose with five ciosin doses ranging from 1.0 to 7.0 mL/kg. Reproductive parameters and plasma levels of 17α-20β-dihydroxy-4-pregnen-3-one (DHP) and PGF2α were evaluated at the time of spawning for both experiments. Neither the timing of ciosin application closer to spawning nor its higher concentrations resulted in increased reproductive parameters or elevated PGF2α and DHP levels. The absence of the PGF2α peak at the time of ovulation in both experiments can be attributed to the rapid increase and subsequent decrease in exogenous PGF2α levels shortly after application. In Experiment 2 two main clusters were observed: one characterized by spawning failure, poor-quality spawn and low DHP levels and the other characterized by successful spawning, high fecundity and elevated DHP levels. Although positive correlations were observed between DHP and good reproductive performance, the reasons behind the substantial variation in DHP among females subjected to the same treatments remain unknown. An emerging focus is to elucidate the pattern of expression of PGF2α receptors and their relationship with DHP in pacu.
Keywords: Ovulation failures; Piaractus mesopotamicus; Prostaglandin synthesis; Spawning induction